Barnets bästa och barnets vilja – särskilt om vårdnad, boende och umgänge - Sunar,Bella (2013)
The term the best interest of the child is not a new concept in the Swedish family law. It is a concept that has developed with time and become more and more adapted to the child's needs. In this paper is initially given a retrospective about the best interests of the child and an insight into how the development has been in the Swedish law. It also takes note of the current legislation for the best interests of the child and the child's will in both Swedish and foreign law. The starting point of this thesis has thus been the best interest of the child and the child's will and how these concepts are being applied on children in cases regarding custody, residence and contact, especially when parents divorce or separate. The child's best interests are, after changes in the custody rules in 2006, decisive in all decisions on matters concerning custody, residence and contact. This is found in The Children and Parents' Code, 6th chapter 2 a §. The principle of the child's best interests is important for the legislation and is available in both Swedish and international law. One issue is that the child's best interests are not easy to define. The principle says that the assessment should take into account the child's need for a close and good contact with both parents. This means that, in custody matters, joint custody is the most appropriate custody form. This assessment must always be done individually, as all cases are different from each other. There are many situations where the only solution, to give the child a safe environment, is sole custody. In this paper, I have chosen to study how the best interests of the child is applied in the law and how the court discusses what really is the best for the child. In addition, I have chosen to study the child's own will and how the child can be heard as it is important when it comes to its future. The principle of the child's best interests, expressed in the UNCRC article 3, stipulates that the child's best interests must be a primary consideration in all matters affecting the child. An important aspect of the principle of the child's best interests is the child's right to be heard in judicial proceedings, and that the child's views are given due weight according to age and maturity. The principle of the child's right to have its opinions heard is expressed in the UNCRC, article 12. In Swedish law, this is expressed in The Children and Parents' Code, 6th chapter 19 §, 5th Para. In Swedish law, there has been some criticism that the courts often do not report the child's will in court judgments and that, once reported, it is often not followed. Thus, an introduction of procedural rights for children should perhaps be made. A discussion of this has been made, for instance in Swedish Government Official Reports 1987:7, where the inquiry found that procedural rights for children would strengthen the child's position in cases concerning custody and access. The child would, according to the inquiry, also have the right to a legal assistant which would assist the child through the process. In the analytical part of the essay follows a discussion regarding two different perspectives of the introduction of procedural rights for children. Firstly, it is about the child being involved in the process relating to matters where the child itself is involved and secondly, about the child being protected in the process and not getting involved in the parents' dispute. Finally it gets concluded that the principle of the child's best interests and the principle of the child's right to be heard correspond better if the child gets procedural rights and thus, the same legal status as its parents.
Keywords: Familjerätt Barnets bästa Barnets vilja Vårdnad; boende och umgänge